Urgensi Perubahan Delik Biasa Menjadi Delik Aduan dan Relevansinya terhadap Perlindungan dan Penegakan Hak Cipta - Hanafi Amrani (Fakultas Hukum Universitas Jambi, 2018)
This article discusses two main issues: first, what is the urgency of the change in nature of offences from ordinary offence to be complaint offence in the copyright law; second, how is the relevance of the change in the nature of the offense to protect and enforce copyright. The urgency of changes in offenses is usually an offense against complaints because copyright is an exclusive right that is personal and civil rights. This personal and civil right indicate the absolute right of the creator or the copyright holder to the results of their work, including the right to report or not to infringe their copyright. Therefore conceptually this personal and civilian nature emphasizes the alignment of mindset that the complaint offence is more appropriately applied to copyright infringement. Whereas the relevance of complaint offence for protection and enforcement of copyright can be seen from the significant role of the creator or copyright holder in the law enforcement process. The creator or copyright holder can play an active role in providing information and evidence of copyright infringement so that the law enforcement process becomes more effective and efficient. Abstrak Artikel ini membahas dua permasalahan pokok: pertama, apa urgensi perubahan delik biasa menjadi delik aduan dalam Undang-undang Hak Cipta; kedua, bagaimana relevansi perubahan sifat delik tersebut terhadap perlindungan dan penegakan hukum hak cipta. Urgensi perubahan delik biasa menjadi delik aduan adalah karena hak cipta merupakan hak eksklusif yang bersifat personal dan keperdataan. Sifat personal dan keperdataan ini mengindikasikan adanya hak mutlak dari pencipta atau pemegang hak cipta atas hasil karya ciptanya, termasuk hak untuk melaporkan atau tidak atas pelanggaran hak ciptanya. Oleh karena itu secara konseptual sifat personal dan keperdataan ini lebih mengedepankan keselarasan pola pikir bahwa delik aduan lebih tepat diterapkan terhadap pelanggaran hak cipta. Sedangkan relevansi delik aduan terhadap perlindungan dan penegakan hak cipta dapat dilihat dari peran yang signifikan dari pencipta atau pemegang hak cipta dalam proses penegakan hukum. Pencipta atau pemegang hak cipta dapat berperan aktif dalam memberikan keterangan dan bukti-bukti dari pelanggaran hak cipta tersebut sehingga proses penegakan hukum dapat berjalan lebih efektif dan efisien.